Pengembangan LKPD Materi Transformasi Geometri dengan Pendekatan Saintifik Berbantuan Geogebra untuk Peserta Didik SMA Kelas XI - Girsang, Melan Kristina; Caswita, Caswita; Wijaya, Agung Putra (FKIP Universitas Mataram, 2025)
This study aims to develop a valid and practical LKPD (Student Worksheet) for use in the mathematics learning process on the topic of geometric transformations. The novelty of this research lies in the integration of the scientific approach and geogebra in teaching geometric transformations. The scientific approach has been proven to enhance problem-solving skills, while geogebra improves concept understanding and problem-solving abilities. The integration of both in the developed LKPD is expected to enhance students' problem-solving skills in an interactive and technology-based manner. The research method used is Research and Development (R&D) with the adaptation of the ADDIE development model. Data collection techniques in this study include interviews, observations, and questionnaires. The data collection instruments consist of interview guidelines, expert validation questionnaires, and response questionnaires. The results of the research have been analyzed and validated in terms of content, media, and language aspects. Additionally, an analysis of the practicality of the LKPD was conducted by teachers and students who used it in the learning process. The validity score for the content aspect from Validator 1 was 80%, categorized as valid, Validator 2 was 71%, categorized as valid, and Validator 3 was 80%, categorized as valid. For media and language aspects, the evaluation from Validator 1 was 66%, categorized as valid, Validator 2 was 61%, and Validator 3 was 85%, categorized as very valid. The analysis of LKPD practicality by teachers and students showed that the LKPD was considered practical, with a practicality score of 84.4% from the teacher (categorized as practical) and 90.8% from the students (categorized as very practical).